Frequency of Infectious Skin Lesions in Kidney Transplant Recipients - Alimagham, Masoomeh; Amini-Afshar, Saeed; Farahmand, Siamak; Pour-Kazemi, Aydin; Pour-Reza-Gholi, Fatemeh; Masood, Sara (Urology Journal, 2009)
Introduction:This study was performed to evaluate the frequency of skin lesions in kidney transplant recipients. Materials and Methods: A total of 681 kidney transplant recipients were followed at Shaheed Labbafinejad transplant center in Tehran, Iran. Skin lesions were evaluated, and diagnoses were made clinically and confirmed by lesion smear, tissue biopsy, tissue culture, and serologic examinations, as indicated. Results: Skin lesions were found in 54 patients (7.9%), and their frequencies were as follows: dermatomal herpes zoster (18 patients, 2.6%, 13 men and 5 women), herpes simplex infection of face and lips (15 patients, 2.2%, 5 men and 10 women), chickenpox (6 patients, 0.9%, 5 men and 1 woman), Kaposi's sarcoma (5 patients, 0.7%, 3 men and 2 women), warts (4 women, 2 of whom had genital warts), pyoderma gangrenosum (1 man, 0.14%), multiple fungal abscesses of the leg (1 man, 0.14%), mucormycosis (1 man, 0.14%), and molluscum contagiosum (1 man, 0.14%). Moreover, 2 women (0.3%) had generalized herpes simplex lesions. Conclusion: Frequencies of herpes zoster (3.5%), herpes simplex (2.5%), and human papillomavirus (0.6%) infections in our kidney transplant recipients were low. We recommend that all kidney transplant candidates be evaluated and immunized for herpes zoster virus before transplantation, all herpetic-form lesions of these patients be reported to physicians (even mild lesions), and finally, that all human papillomavirus lesions be diagnosed and treated promptly to prevent more serious lesions such as malignancies.